Effect of Environmental Temperature in Lowlands on Lung Health: A Literature Review - Nurlinda Nur; Bafirman; Gusril; Donal Syafrianto; Dally Rahman; Fiky Zarya (Jurnal Penelitian Pendidikan IPA, 2023)
Lowlands, with their hot and humid climates, present health challenges especially on the respiratory system. High ambient temperatures can worsen lung conditions, especially for people with asthma or chronic obstructive pulmonary disease (COPD). In the context of climate change and increased air pollution, it is important to understand the impact of environmental temperature on lung health in lowlands. The study aimed to review the existing literature to evaluate these effects, focusing on the mechanisms underlying this relationship and the long-term effects of high temperature exposure on lung function. The method used was a systematic literature review, which included relevant studies from scientific journals on the relationship between environmental temperature and lung health, as well as epidemiological studies in lowland populations. The article search technique in this study is through web access to Mendeley, and Science Direct. The results showed that high temperatures could trigger exacerbations of lung diseases, increase pollutant particles, and decrease lung function, as well as increase the risk of respiratory infections and decrease quality of life. In conclusion, high temperatures in lowlands have a significant impact on lung health, requiring mitigation efforts, and further research to understand the underlying biological mechanisms and develop effective intervention strategies.